Pengaruh Iklim Kerja Terhadap Kinerja Guru Di SMP Negeri 3 Bantan - Nayli Marzuqoh; Andriesgo, Johan (Jurnal Kependidikan Islam, 2024)
The aim of this research is to explore how the work environment affects the performance of teachers at SMP Negeri 3 Bantan. The motivation behind this study stems from the observation that some teachers are not fully optimizing their preparation for teaching. This deficiency becomes apparent in the classroom, where students are often tasked with notetaking without adequate explanation from the teacher. Furthermore, a portion of teachers lacks diversity in their teaching methods, resulting in a monotonous and uninspiring learning atmosphere. Additionally, many teachers demonstrate a lack of punctuality in their attendance, which disrupts the efficiency of the teaching process. Employing a quantitative approach, this study encompasses all teachers at SMP Negeri 3 Bantan, focusing on the interplay between work climate and teacher performance. The sample size consists of 20 individuals, with data collected through questionnaires, observations, and documentation. Analysis involves quantitative descriptive statistics and simple linear regression. Findings reveal a highly positive work climate at SMP Negeri 3 Bantan, with teacher performance also rated highly. Moreover, the study highlights the significant influence of the work climate on teacher performance, with 43.7% of performance variance attributed to this factor. The regression equation derived from the results indicates a positive relationship between work climate and teacher performance. Statistical tests confirm the rejection of the null hypothesis, affirming the acceptance of the alternative hypothesis.